Efektivitas Media Flip Fold untuk Meningkatkan Kemampuan Melipat Baju bagi Anak Down Syndrome - Adinda Maurelia; Kasiyati Kasiyati (Jurnal Penelitian Pendidikan Khusus, 2022)
This study aims to prove whether flip fold media can improve the ability to fold clothes in children with Down syndrome. This study uses an experimental research type in the form of Single Subject Research (SSR) with an A-B-A design. The data analysis technique used was graphical visual analysis. The results of data analysis from 18 observations in 3 conditions, namely at baseline (A1) obtained results of 8%, 17%, 25%, 25%, 25%, 25%. In the intervention (B) the results were 38%, 46%, 50%, 54%, 67%, 79%, 79%, 79%. Finally, at the baseline (A2) the results were 75%, 83%, 88%, 88 %, 88%. The results showed that the ability to fold clothes increased after using flip fold media in children with Down syndrome class III/C at the Karya Inspirasi Mandiri Foundation